If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 6(x + 8) + -4(x + -2) = 26 Reorder the terms: 6(8 + x) + -4(x + -2) = 26 (8 * 6 + x * 6) + -4(x + -2) = 26 (48 + 6x) + -4(x + -2) = 26 Reorder the terms: 48 + 6x + -4(-2 + x) = 26 48 + 6x + (-2 * -4 + x * -4) = 26 48 + 6x + (8 + -4x) = 26 Reorder the terms: 48 + 8 + 6x + -4x = 26 Combine like terms: 48 + 8 = 56 56 + 6x + -4x = 26 Combine like terms: 6x + -4x = 2x 56 + 2x = 26 Solving 56 + 2x = 26 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-56' to each side of the equation. 56 + -56 + 2x = 26 + -56 Combine like terms: 56 + -56 = 0 0 + 2x = 26 + -56 2x = 26 + -56 Combine like terms: 26 + -56 = -30 2x = -30 Divide each side by '2'. x = -15 Simplifying x = -15
| .05x-2+2x=3x-.95x+3 | | b^2+3=19 | | -4y+7=-10y+37 | | 9-(x+18)=-x-7 | | 105+25h=180 | | 30-6n=-12+9n | | 7m-5(m+1)=2(3-m)-5 | | -3z+8(z+y)=0 | | 5x+6+2x-1=10+3 | | 7x-12=5x+6 | | 27=6s-9 | | -29=-3x-3x+1 | | 180+105=25h | | 5m=-40 | | -3(x+4)-21x=21 | | 7x+14+8x+6=180 | | 4x+2(x-7)=-8 | | 7x-12=4x-15 | | 5+0+0.01= | | y=x^2+x-20 | | 8x+6-9=2-x-15 | | 21x^2-97x+63=0 | | 2+7x+5x=50 | | -3(8-7a)=-4(1-4a) | | 11.50x=409.50 | | 14x+17+19x=-255 | | 0.05(0.3m+35n)-0.8(-0.09m-22m)= | | v^8=2 | | 2x+3/4(4x+16)=17 | | 14n+12=24 | | 6d+3=5d | | -8(3b+2)+(25b-8)=0 |